LRRK2-mediated NLRC4 phosphorylation differentially regulates IL-1β/IL-18 secretion - Deloer, Sharmina; Fuss, Ivan; Gough, Portia; Debebe, Anketse; Picker, Mellissa; Devita, Robert J.; Peter, Inga; Strober, Warren (Frontiers in Immunology, 2025)
In the present study, we explored the relation of LRRK2-kinase phosphorylation of the NLRC4 inflammasome to NLRC4 inflammasome function in normal humans and mice, as well as in patients with Crohn’s disease (CD). We found that LRRK2-kinase was both necessary and sufficient for NLRC4 phosphorylation in human mononuclear cells and likely in murine mononuclear cells as well. In addition, such phosphorylation requires ASC association with the nascent NLRC4 inflammasome and is necessary for ASC function. Finally, we found that inhibition of LRRK2-kinase phosphorylation of NLRC4 impairs inflammasome IL-1β production but has little to no effect on its IL-18 production. The mechanism of this dichotomy was revealed in studies of NLRC4 inflammasome activity, showing that pro-IL-1β cleavage is partially dependent on LRRK2-mediated ASC binding and cleavage function, whereas pro-IL-18 is independent of such ASC function. In accompanying studies of circulating cells from patients with CD, a disease associated with LRRK2 polymorphisms that affect LRRK2 expression, we showed that patient cells exhibited increased NLRC4 inflammasome activation; in addition, inhibition of LRRK2-kinase impaired IL-1β secretion but had little or no effect on IL-18 secretion by patient cells. Finally, studies of WT mice or mice with epithelial cell-specific NLRC4 deletion revealed that NLRC4 inflammasome activation causes impairment of gut barrier function that is abrogated by inhibition of LRRK2-kinase activity. Thus, NLRC4 inflammasome function is increased in CD, and its regulation by an LRRK2-kinase inhibitor is calibrated to prevent NLRC4-mediated barrier dysfunction.